2006
DOI: 10.1002/app.23246
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of water soluble polymers and their binary blends

Abstract: ABSTRACT:The effect of five different metal oxides on the pyrolysis of poly(ethylene oxide) (PEO), polyacrylamide (PAM), and poly(vinyl alcohol) (PVA) was investigated using thermogravimetry. The presence of metal oxide did not influence the degradation of PEO while the order of metal oxide on the degradation rate of PAM and PVA was PbO Ͼ Co 3 O 4 Ͼ CuO Ͼ ZnO Ͼ Al 2 O 3 . The miscibility and the decomposition of PEO-PAM and PVA-PAM blends were also investigated. The blends were found to be immiscible and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Here the first moment over the end-point distribution of both the PEO as well as the PVOH polymers, h g , is plotted versus v PVOH-W. In panels c-f the volume fraction profiles u(x,z) for PEO and PVOH are shown for a special case: v PEO-PVOH = 0.4 and v PVOH-W = 0.52 potentially resembling the experimental situation, as described above, where the solvent quality of PVOH is marginal, that of PEO is slightly better, and PEO and PVOH are rather incompatible [37,44,45]. Note that we purposely neglected potential disparities in surface affinity et cetera, as they are, to the best of our knowledge, not known for the system.…”
Section: Self-consistent Field Calculationsmentioning
confidence: 83%
See 2 more Smart Citations
“…Here the first moment over the end-point distribution of both the PEO as well as the PVOH polymers, h g , is plotted versus v PVOH-W. In panels c-f the volume fraction profiles u(x,z) for PEO and PVOH are shown for a special case: v PEO-PVOH = 0.4 and v PVOH-W = 0.52 potentially resembling the experimental situation, as described above, where the solvent quality of PVOH is marginal, that of PEO is slightly better, and PEO and PVOH are rather incompatible [37,44,45]. Note that we purposely neglected potential disparities in surface affinity et cetera, as they are, to the best of our knowledge, not known for the system.…”
Section: Self-consistent Field Calculationsmentioning
confidence: 83%
“…The corona forming polymer blocks are rather incompatible, as was the case in the Janus-micelles containing the relatively immiscible PAAm/PEO pair. In macroscopic systems, immiscibility of PEO and PVOH chains was reported for binary blends [44,45], while Wanchoo et al found the ternary PEO (565 kg mol À1 )/PVOH (127 kg mol À1 )/salt-free water system to satisfy four previously posed criteria for miscibility [46]. Apart from the obvious difference in block chemistry between PVOH and PAAm, there is another important difference between the previously investigated and the current system, namely the relative size and abundance of the immiscible corona blocks and the overall shape of the micelle.…”
Section: Corona Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Polyamides are known for potential applications where the properties of thermal stability and fire resistance are necessary to be controlled [1][2][3][4]. Several articles are available to prove the great impact of the thermal stability of polymers on blending [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These defects are predominantly acetate residuals, due to incomplete hydrolysis of polyvinyl acetate used for PVA fabrication. It is known that the excitation of macromolecules typically initiates various types of photo-activated reactions in polymers, such as chain scission [16,17], formation of chromophore groups and free radicals [18][19][20][21], breaking of intermolecular bonds [17], configurational transformations [22], etc. In full agreement with these earlier observations, our transmittance and PL results demonstrate (Figures 2 and 3) the appearance in the unloaded PVA of new UV-induced moieties that absorb, scatter, and emit light (see Figure 4c).…”
Section: Resultsmentioning
confidence: 99%